2011
DOI: 10.1016/j.actbio.2010.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Differences between top-down and bottom-up approaches in mineralizing thick, partially demineralized collagen scaffolds

Abstract: Biominerals exhibit complex hierarchical structures derived from bottom-up self-assembly mechanisms. Type I collagen serves as the building block for mineralized tissues such as bone and dentin. In the present study, 250-300 μm thick, partially-demineralized collagen scaffolds exhibiting a gradient of demineralization from the base to surface were mineralized using a classical top-down approach and a non-classical bottom-up approach. The top-down approach involved epitaxial growth over seed crystallites. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
114
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 49 publications
1
114
0
4
Order By: Relevance
“…The development of self-sealing dentine bonding systems with therapeutic ability to create a chemical bond in addition to the micromechanical one, enabling dental restorations to have longer lifetimes, is currently one of the main targets of dental biomaterials research 47) .…”
Section: Development Of Dentine Bonding Systems Comprising Bioactive mentioning
confidence: 99%
“…The development of self-sealing dentine bonding systems with therapeutic ability to create a chemical bond in addition to the micromechanical one, enabling dental restorations to have longer lifetimes, is currently one of the main targets of dental biomaterials research 47) .…”
Section: Development Of Dentine Bonding Systems Comprising Bioactive mentioning
confidence: 99%
“…The biomimetic mineralization through this process is called intrafibrillar mineralization. 8,9,14,[25][26][27] In contrast to the classical crystallization pathways, the nonclassical crystallization route involves mesoscopic transformations of self-assembled, metastable, or amorphous precursor particles into nanoparticulate superstructures. 28,29 Because this process assembles materials from the nanoscopic scale to large sizes, it is also called the bottom-up strategy.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Because this process assembles materials from the nanoscopic scale to large sizes, it is also called the bottom-up strategy. 8,30 Many previous experiments and studies have shown that biomineralization is a bottom-up process based on the theory of nonclassical crystallization. 8,28,31 The key of the PILP process is to find negatively charged polymers for stabilizing amorphous precursor particles to achieve liquid-liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, even with EDTA agents, it seems that a volume of demineralized and non-resin infiltrated collagen remains at the base (bottom) of the hybrid layer 8 . If effective inhibitors of MMPs are included in resin-dentin bonding interfaces, they may protect the seed crystallite-sparse collagen fibrils of the scaffold from degradation, and they could be remineralized 9 .…”
Section: Introductionmentioning
confidence: 99%